Functioning of self‐help groups in India: Members' perceptions of key issues. Issue 2 (21st March 2017) - Huma,; Hasan, Abid
Abstract : Self‐help group‐bank linkage program is considered a powerful tool for eradicating poverty in many poor and developing countries, especially in Asia. The number of these groups has increased rapidly during the last few years; however, their efficacy to achieve long‐term poverty alleviation has been questioned by many researchers. Previous studies have focused mainly on objective indicators to understand the program's impact on the lives of its members, such as changes in the economic condition and the development of conceptual frameworks. The present study primarily focuses on member perceptions of the overall functioning of the self‐help group. A questionnaire survey was administered to 15 presidents and 75 group members belonging to 15 self‐help groups with active bank accounts in Chandigarh, a union territory of India. Drawing on their responses and perceptions, the five major problems faced by these groups were identified as: (i) ineffective group meetings, (ii) absence of income‐generating activities, (iii) lack of cooperation among members, (iv) lack of awareness, and (v) minimal savings. Our key recommendations include: (i) increased organizational support, (ii) focus on skill development, (iii) training and motivation, (iv) effective leadership, and (v) regular meetings.